2014
DOI: 10.1007/s40620-014-0077-9
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal assessment of the natural rate of decline in renal function with age

Abstract: This large longitudinal study provides new data on the decrease in eGFR with age. Accurate prediction of the natural rate of GFR decline might be used to distinguish between normally aging kidneys and those with chronic disease. This approach could avoid unnecessary diagnostic procedures in the former and facilitate appropriate treatment in the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
66
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 28 publications
11
66
0
3
Order By: Relevance
“…The decline may be related to CKD progression, as it has been reported that during 8-12 years of follow-up, kidney function decline progressed in one third of patients with type 1 diabetes and microalbuminuria with normal or elevated baseline GFR (19). We reported that the absolute annual eGFR decline of 3.0 ml/min per 1.73 m 2 in participants with eGFR$90 ml/min per 1.73 m 2 was three times higher in this "healthy," relatively young group than reported in studies from other populations (14,20). The relatively high rate of eGFR decline in the current study is consistent with higher rates of ESRD among indigenous Australians, with likely multiple contributory factors ranging from socioeconomic disadvantage, early life insults (low birthweight, post-streptococcal GN, recurrent infections), high rates of cigarette smoking, and high rates of metabolic syndrome and diabetes among this high-risk population (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 51%
“…The decline may be related to CKD progression, as it has been reported that during 8-12 years of follow-up, kidney function decline progressed in one third of patients with type 1 diabetes and microalbuminuria with normal or elevated baseline GFR (19). We reported that the absolute annual eGFR decline of 3.0 ml/min per 1.73 m 2 in participants with eGFR$90 ml/min per 1.73 m 2 was three times higher in this "healthy," relatively young group than reported in studies from other populations (14,20). The relatively high rate of eGFR decline in the current study is consistent with higher rates of ESRD among indigenous Australians, with likely multiple contributory factors ranging from socioeconomic disadvantage, early life insults (low birthweight, post-streptococcal GN, recurrent infections), high rates of cigarette smoking, and high rates of metabolic syndrome and diabetes among this high-risk population (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 51%
“…One possibility is that compensatory hypertrophy of residual nephrons maintains eGFR in some elderly populations [31]. This could explain (at least to some extent) the inter-individual differences seen in eGFR in elderly populations [32-34]. …”
Section: Structural and Functional Changes In Renal Ageingmentioning
confidence: 99%
“…Multiple studies report variable age-associated decline in eGFR from 0.4-2.6 ml/min/year [33, 34, 36, 43, 44]. The rate of decline increases with age.…”
Section: Structural and Functional Changes In Renal Ageingmentioning
confidence: 99%
“…Hekimlerin, yaşlıların tedavisinde, sayılan bu özelliklerin gereklerine uygun davranması şarttır. [47][48][49][50][51][52] Bu yaş grubunda eşlik eden hastalıklar nedeni ile ilaç kullanımı daha fazla olduğundan, hastaya verilmesi planlanan antibiyotiğin, kullanılmakta olan diğer ilaçlarla olası etkileşimi de göz önünde bulundurulmalıdır. Bununla birlikte, yaşlılarda meydana gelen birtakım fizyolojik değişiklikler nedeni ile antibiyotiklerin emilim, dağılım, proteinlere bağ-lanma ve eliminasyonu etkilenebilmektedir.…”
Section: Yaşlilarda Anti̇bi̇yoti̇k Kullanimiunclassified
“…51 Ayrıca, yaşla birlikte böbrek fonksiyonları da azalmaktadır. 52 Diş hekimliğinde kullanılan yukarıda sözü edilen antibiyotiklerin karaciğer-den metabolize edilerek ve/veya böbreklerden atılarak elimine edildiği bilinmektedir. Dolayısıyla yaşlılıkta antibiyotiklerin eliminasyonunda yetersizlik oluşabileceği ve buna bağlı yan/karşıt etki sıklık ve şiddetinin artabileceği göz önünde bulundurulmalı, tedavi mümkün olduğunca bireyselleş-tirilmelidir.…”
Section: Yaşlilarda Anti̇bi̇yoti̇k Kullanimiunclassified